Work study in factory (cable slack making operation) / Mohd Nazlizan Ibrahim, Norhissham Abdul Hamid and Wan Nazrul Faizal Wan Mohamad - Ibrahim, Mohd Nazlizan; Abdul Hamid, Norhissham; Wan Mohamad, Wan Nazrul Faizal (Faculty of Mechanical Engineering, 2002)
Work study is the systematic analysis of all facets of a job with the objective of arranging it so that maximum efficiency is obtained from labor, plant, equipment, materials and supervision. It achieves this by detailed examination and recording of all the various aspects of the job so that all relevant information will be brought to light and presented to management to enable them to make the right decisions instead of using intuitive guess work. The human aspect is the most important part of work-study, both on site and at higher management level and the subject consist just as much of human relations as it does of techniques.